The role of IGF-1 in exercise to improve obesity-related cognitive dysfunction - He, Yimin; Wang, Qian; Wu, Huaduo; Dong, Yumo; Peng, Zifu; Guo, Xiangyin; Jiang, Ning (Frontiers in Neuroscience, 2023)
Obesity is an important factor that threatens human health. The occurrence of many chronic diseases is related to obesity, and cognitive function decline often occurs with the onset of obesity.With the further prevalence of obesity, it is bound to lead to a wider range of cognitive dysfunction(ORCD). Therefore, it is crucial to suppress ORCD through intervention. In this regard, exercise has been shown to be effective in preventing obesity and improving cognitive function as a non-drug treatment. There is sufficient evidence that exercise has a regulatory effect on a growth factor closely related to cognitive function -insulin-like growth factor 1 (IGF-1).IGF-1 may be an important mediator in improving ORCD through exercise. This article reviews the effects of obesity and IGF-1 on cognitive function and the regulation of exercise on IGF-1. It analyzes the mechanism by which exercise can improve ORCD by regulating IGF-1. Overall, this review provides evidence from relevant animal studies and human studies, showing that exercise plays a role in improving ORCD. It emphasizes the importance of IGF-1, which helps to understand the health effects of exercise and promotes research on the treatment of ORCD.